Pharmacokinetics of Five Alkaloids and their Metabolites in Normal and Diabetic Rats after Oral Administration of Rhizoma coptidis - Feng, Xinchi; Wang, Kun; Cao, Shijie; Ding, Liqin; Qiu, Feng (Planta Medica, 2021)
Rhizoma coptidis has been clinically used for a long time for the treatment of various diseases in China, such as hypertension, diabetes, and inflammation. Previous studies have shown that alkaloid components of Rhizoma coptidis extract could be extensively metabolized and the metabolites were also considered to be the therapeutic material basis. However, until now, pharmacokinetic studies of the in vivo metabolites have not been revealed yet. The aim of the present study was to characterize the pharmacokinetics and excretions of five main alkaloids (berberine, jatrorrhizine, palmatine, epiberberine, and coptisine) and their seven metabolites (berberrubine, demethyleneberberine, jatrorrhizine-3-O-β-D-glucuronide, thalifendine-10-O-β-D-glucuronide, berberrubine-9-O-β-D-glucuronide, demethyleneberberine-2-O-sulfate, and demethyleneberberine-2-O-β-D-glucuronide) in rats after oral administration of Rhizoma coptidis extract. Meanwhile, comparative pharmacokinetics and excretions of these analytes in diabetic model rats were also investigated, since Rhizoma coptidis is widely used for the treatment of diabetes. Our results showed that the in vivo existing forms of alkaloid components were phase II metabolites, highlighting the glucuronidation metabolic pathway. In diabetic model rats, the utilization of Rhizoma coptidis alkaloids was significantly increased and the biotransformation of berberine into berberrubine was significantly inhibited.
Keywords: Coptis chinensis; Ranunculaceae; pharmacokinetics; excretion; diabetic rats; phase II metabolites